Sosialisasi Edukasi serta Pentingnya Konservasi Geodiversity Kepada Masyarakat Desa Jari - Indriani, Yulia; Fadilah, Rifqo’ Nur; Aji Prayogo, Dimas Priyo; Saprita, Riri; Endriani, Diah (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
A community service activity through educational outreach on geodiversity conservation was conducted in Jari Village, Gondang District, Bojonegoro Regency, East Java. Jari Village has two potential geosites: the "Banyu Wedang" hot spring and the "Selo Gajah" stone altar, a relic of the ancient civilization. These sites offer educational, aesthetic, and economic value through geotourism development. However, this potential has not been optimally utilized due to limited public understanding and a lack of promotion as a geosite-based tourist destination. This activity aims to increase public awareness and active participation in protecting and managing the geosites as village assets with conservation value. The activity included lectures, interactive discussions, and a question-and-answer session. Speakers from the Bojonegoro Regional Planning and Development Agency (BAPPEDA) presented material on the importance of geodiversity conservation and its relationship to sustainable village development. The activity was met with enthusiasm from the community, as evidenced by the high number of participants attending and actively participating in discussions on the use of geosites for geotourism. The results of the activity indicated an increase in community understanding of the geopark concept, the benefits of geosite conservation, and the opportunities for village economic development through geotourism. With this activity, it is hoped that the community will not only be observers, but also become drivers in biodiversity conservation efforts and promoters of local tourism.